2022
DOI: 10.1038/s41598-022-19226-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between hypothyroidism and proteinuria in patients with chronic kidney disease: a cross-sectional study

Abstract: Hypothyroidism is known to be correlated with kidney function and nephrotic range proteinuria. However, it is uncertain whether non-nephrotic proteinuria is associated with hypothyroidism. This study aimed to evaluate the association of proteinuria and hypothyroidism in chronic kidney disease (CKD) patients. We conducted a cross-sectional study composed of 421 CKD patients in a single hospital with measurements of 24-h urine protein excretion (UP) and thyroid function tests. Spearman correlation analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Various factors related to CKD may affect these processes. It has been reported that FT3 levels are more associated with kidney function compared with FT4 ( 23 ), which is in agreement with the result of this study. Although FT4 is more common to be taken in clinical than FT3, FT3 should be checked when considering the relationship with kidney function.…”
Section: Discussionsupporting
confidence: 93%
“…Various factors related to CKD may affect these processes. It has been reported that FT3 levels are more associated with kidney function compared with FT4 ( 23 ), which is in agreement with the result of this study. Although FT4 is more common to be taken in clinical than FT3, FT3 should be checked when considering the relationship with kidney function.…”
Section: Discussionsupporting
confidence: 93%